Metode Drill pada Kecakapan Numerik Siswa Kelas VI, Konstribusi Kampus Mengajar-2 di SDN 02 Klepu, Semarang - Yusida - Lusiana; wisnu - Widjanarko (Universitas Pendidikan Indonesia, 2023)
Numerical skills become one of the important pillars in the world of education that should be mastered well by children since elementary school. However, in reality the number of children in Indonesia is still relatively low. Therefore, the government through the Teaching Campus program has made efforts to improve learning related to numeracy in various elementary and junior high schools. One of these activities took place at SDN 02 Klepu, Semarang, Central Java, which was attended by 22 grade VI students. This paper aims to describe the role of the Teaching Campus in increasing student numeracy. The method used is pre-experimental designs with the type of one group pretest-posttest, observation, and literature study. The treatment process for students is carried out by strengthening and repeating basic Mathematics material according to Piaget's theory of cognitive development using the drill method. The results found that the method applied was able to help students to better remember and understand various mathematical problems.